Polyester pellet, molded body, and film

By creating polyester pellets with specific intrinsic viscosity ranges using ethylene glycol derived from carbon monoxide or carbon dioxide, the challenge of achieving comparable mechanical properties in molded bodies and films is addressed, while also reducing environmental impact.

JP2025054171APending Publication Date: 2025-04-07DAI NIPPON PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024101528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-25
Filing Date
2024-06-24
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

There is a lack of clarity on whether polyester molded bodies or films produced using ethanol made from carbon monoxide gas or ethylene glycol made from carbon dioxide gas exhibit the same mechanical properties as those produced from conventional petroleum-derived or biomass raw materials.

Method used

The development of polyester pellets with an intrinsic viscosity of 0.50dL/g or more and 0.90dL/g or less, made from ethylene glycol produced from carbon monoxide or carbon dioxide, which are suitable for processing into molded bodies and films.

Benefits of technology

The proposed solution reduces environmental impact and provides polyester pellets suitable for processing into molded bodies and films with comparable mechanical properties to conventional products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054171000001_ABST
    Figure 2025054171000001_ABST
Patent Text Reader

Abstract

To provide a polyester pellet that can reduce environmental load and is suitable for processing into a molded body and a film.SOLUTION: The polyester pellet of the present disclosure includes a polyester composed of diol units and dicarboxylic acid units, the diol units including ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide, and has an intrinsic viscosity of 0.50 dL / g or more and 0.90 dL / g or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polyester pellets, molded articles, and films. [Background technology]

[0002] Polyesters are widely used in various industrial applications because they are inexpensive and have excellent mechanical properties, chemical stability, heat resistance, transparency, etc. Polyesters are obtained by polycondensation of diol units and dicarboxylic acid units. For example, polyethylene terephthalate is produced by esterifying ethylene glycol and terephthalic acid as raw materials and then polycondensing them. These raw materials are produced from petroleum, which is a fossil resource. For example, ethylene glycol is industrially produced from ethylene, and terephthalic acid is industrially produced from xylene.

[0003] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a desire to move away from fossil fuels in the materials field, just as there is in energy, and the production of polyester from raw materials other than fossil fuels, such as biomass, is being considered. Biomass is a non-exhaustible resource, an industrial resource originating from the constituent substances of living organisms. The carbon contained in biomass is derived from carbon dioxide absorbed from the atmosphere by photosynthesis during the growth of organisms, so even if carbon dioxide is emitted by burning biomass, it is thought that the amount of carbon dioxide in the atmosphere is not increased overall. For this reason, biomass is attracting attention as a carbon-neutral renewable energy source. Recently, the practical application of biomass plastics made from these biomass raw materials has progressed rapidly, and attempts have been made to produce polyester, a general-purpose polymer material, from these biomass raw materials (for example, Patent Documents 1 and 2). By using polyester produced from biomass-derived raw materials (biomass polyester) instead of polyester produced using raw materials derived from fossil fuels, it becomes possible to reduce the amount of fossil fuel used and the environmental burden.

[0004] Bioethanol, which is used to manufacture biomass polyester, is generally produced by sugar fermentation from edible raw materials such as corn. However, it is known from experience that the yield of crops such as sugarcane is greatly affected by meteorological factors. Therefore, there are concerns that climate change will make it difficult to stably procure sugarcane, the raw material for bioethanol. Ethanol, which is also used as a raw material for plastics, has been produced from resources that are neither fossil fuels nor biomass. For example, ethanol has been produced by microbial fermentation using carbon monoxide present in exhaust gases generated from steelworks and factories as a raw material (e.g., Patent Document 3). Ethylene glycol has also been produced by electrolyzing carbon dioxide present in exhaust gases generated from steelworks and factories (e.g., Patent Document 4). Furthermore, production of polyesters from these compounds has also been considered. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2011-527348 [Patent Document 2] Special Publication No. 2012-519748 [Patent Document 3] Special Publication No. 2011-512869 [Patent Document 4] JP 2018-123390 A Summary of the Invention [Problem to be solved by the invention]

[0006] It has been conventionally practiced to manufacture molded bodies such as bottles and films from polyesters produced from petroleum-derived raw materials or from polyesters produced from biomass raw materials. However, it was not clear whether molded bodies and films produced from polyesters produced using ethanol produced from carbon monoxide gas or ethylene glycol produced from carbon dioxide gas would exhibit mechanical properties similar to those of conventional molded bodies and films.

[0007] The present inventors have discovered that polyester pellets produced using ethylene glycol produced from carbon monoxide gas or carbon dioxide gas as a raw material have a predetermined intrinsic viscosity and are suitable for processing into molded articles such as bottles and films. The present disclosure was completed based on this knowledge and through further investigation.

[0008] Therefore, an object of the present disclosure is to provide polyester pellets that can reduce the environmental load and are suitable for processing into molded articles and films. Another object of the present disclosure is to provide molded articles and films using the polyester pellets. [Means for solving the problem]

[0009] The present disclosure is solved by the following embodiments. <1> A polyester pellet comprising a polyester consisting of a diol unit and a dicarboxylic acid unit, The diol unit contains ethylene glycol produced from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide, A polyester pellet having an intrinsic viscosity of 0.50 dL / g or more and 0.90 dL / g or less. <2> The dicarboxylic acid unit includes at least one selected from the group consisting of terephthalic acid derived from a fossil fuel, terephthalic acid derived from biomass, and terephthalic acid derived from carbon dioxide gas. <1> 2. The polyester pellet according to claim 1 . <3> The Kjeldahl nitrogen content is 260 μg / g or less. <1> or <2> 2. The polyester pellet according to claim 1 . <4> The carbon dioxide molecule content is 4.8 x 10 17 pcs / g or more 3.0×10 18 pcs / g or less, <1> ~ <3> 13. The polyester pellet according to claim 12, <5> The water molecule content is 1.8 x 10 19 pcs / g or more 1.0×10 20 pcs / g or less, <1> ~ <4> 13. The polyester pellet according to claim 12, <6> <1> ~ <5> 2. A molded article using the polyester pellets according to claim 1. <7> <1> ~ <5> A film using the polyester pellets according to any one of the above items. Effect of the Invention

[0010] The present disclosure can provide polyester pellets that can reduce the environmental load and are suitable for processing into molded articles and films. The present disclosure also provides a molded article and a film using the polyester pellets. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic half-sectional view showing one embodiment of a preform used in producing a molded article according to the present disclosure. [Diagram 2] FIG. 1 is a schematic half-sectional view showing one embodiment of a molded body according to the present disclosure. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing one embodiment of a film according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [polyester] The polyester constituting the polyester pellet according to the present disclosure is composed of diol units and dicarboxylic acid units, and is obtained by a polycondensation reaction using ethylene glycol as the diol units and dicarboxylic acid as the dicarboxylic acid units, which are derived from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide.

[0013] Ethylene glycol using carbon monoxide gas as a raw material can be produced from ethanol produced using carbon monoxide gas as a raw material. For example, ethylene glycol using carbon monoxide gas as a raw material can be obtained by, for example, producing ethylene glycol from ethanol produced using carbon monoxide gas as a raw material by a conventionally known method via ethylene oxide.

[0014] <Microbial fermentation> Ethanol, which is made from carbon monoxide gas, can be obtained by microbial fermentation.

[0015] Microbial fermentation is carried out, for example, in a fermenter filled with a culture solution containing water and microorganisms. A raw material gas containing carbon monoxide gas is supplied into the fermenter, and the carbon monoxide gas is converted into ethanol inside the fermenter. The raw material gas may contain carbon dioxide, nitrogen, oxygen, etc. in addition to carbon monoxide.

[0016] The fermenter is preferably a continuous fermentation apparatus, and may be any of agitation type, airlift type, bubble column type, loop type, open bond type, and photobio type. The raw material gas and the culture solution may be continuously supplied to the fermenter, but it is not necessary to supply the raw material gas and the culture solution simultaneously, and the raw material gas may be supplied to the fermenter to which the culture solution has been previously supplied. The raw material gas is generally blown into the fermenter through a sparger or the like.

[0017] The culture medium is not particularly limited as long as it has an appropriate composition for culturing microorganisms, but is a liquid containing water as the main component and nutrients (e.g., vitamins, phosphoric acid, etc.) dissolved or dispersed in the water.

[0018] The temperature of the fermenter is preferably controlled to 40° C. or lower. By controlling the temperature to 40° C. or lower, the microorganisms in the fermenter do not die, and ethanol is efficiently produced by contacting the raw material gas with the microorganisms. The temperature of the fermenter is more preferably 38° C. or lower, and in order to enhance the activity of the microorganisms, is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.

[0019] The microorganism (species) that ferments the raw gas is not particularly limited as long as it can produce ethanol by microbial fermentation of the raw gas using carbon monoxide as the main raw material. For example, the microorganism (species) is preferably one that produces ethanol from the raw gas by the fermentation action of gas-utilizing bacteria. Among gas-utilizing bacteria, the genus Clostridium is preferred from the viewpoint of gas utilization and culture stability, and Clostridium autoethanogenum is more preferred. Examples are given in more detail below.

[0020] Gas-utilizing bacteria include both Eubacteria and Archaea. Examples of eubacteria include bacteria of the genus Clostridium, Moorella, Acetobacterium, Carboxydocella, Rhodopseudomonas, Eubacterium, Butyribacterium, Oligotropha, Bradyrhizobium, and the aerobic hydrogen-oxidizing bacteria Ralsotonia.

[0021] On the other hand, examples of archaea include bacteria of the genus Methanobacterium, bacteria of the genus Methanobrevibacter, bacteria of the genus Methanocalculus, bacteria of the genus Methanococcus, bacteria of the genus Methanosarcina, bacteria of the genus Methanosphaera, bacteria of the genus Methanothermobacter, Metha Examples include bacteria of the genus Nothrix, bacteria of the genus Methanoculleus, bacteria of the genus Methanofollis, bacteria of the genus Methanogenium, bacteria of the genus Methanospirillium, bacteria of the genus Methanosaeta, bacteria of the genus Thermococcus, bacteria of the genus Thermofilum, bacteria of the genus Arcaheoglobus, and the like. Among these, as archaea, bacteria of the genus Methanosarcina, bacteria of the genus Methanococcus, bacteria of the genus Methanothermobacter, bacteria of the genus Methanothrix, bacteria of the genus Thermococcus, bacteria of the genus Thermofilum, and bacteria of the genus Archaeoglobus are preferred.

[0022] Furthermore, because of their excellent carbon monoxide and carbon dioxide assimilation ability, archaea are preferably Methanosarcina bacteria, Methanothermobactor bacteria, or Methanococcus bacteria, and more preferably Methanosarcina bacteria or Methanococcus bacteria. Specific examples of Methanosarcina bacteria include Methanosarcina barkeri, Methanosarcina mazei, and Methanosarcina acetivorans.

[0023] Among the gas-utilizing bacteria described above, it is preferable to select and use bacteria with high ethanol production ability, such as Clostridium autoethanogenum, Clostridium ljungdahlii, Clostridium aceticum, Clostridium carboxidivorans, Moorella thermoacetica, and Acetobacterium woodii.

[0024] Ethanol produced by microbial fermentation is obtained, for example, as an ethanol-containing liquid mixed with a culture liquid. Ethanol can be separated from this ethanol-containing liquid using a separation device. Examples of separation devices include solid-liquid separation devices, distillation devices, and separation membranes, and it is preferable to use a combination of a solid-liquid separation device and a distillation device. The separation process performed by combining a solid-liquid separation device and a distillation device will be specifically described below.

[0025] The ethanol-containing liquid obtained by microbial fermentation is separated into a solid component mainly composed of microorganisms and a liquid component containing ethanol in a solid-liquid separation device. The ethanol-containing liquid obtained by microbial fermentation contains, in addition to the target ethanol, microorganisms contained in the fermenter and their dead bodies as solid components, so solid-liquid separation is performed to remove these. Examples of solid-liquid separation devices include filters, centrifuges, and devices that use a solution precipitation method. The solid-liquid separation device may also be a device (e.g., a heat drying device) that evaporates the liquid component containing ethanol from the ethanol-containing liquid and separates it from the solid component. At this time, all of the liquid component containing the target ethanol may be evaporated, or the liquid component may be partially evaporated so that the target ethanol is preferentially evaporated.

[0026] The liquid component separated by solid-liquid separation is further distilled in a distillation apparatus to separate the desired ethanol. Separation by distillation makes it possible to purify ethanol in large quantities to a high purity with a simple operation. When distillation is performed, a known distillation apparatus such as a distillation column may be used. In addition, the distillation is performed, for example, so that the distillate contains the target ethanol at a high purity, while the bottoms (i.e., distillation residue) contains water as a main component (for example, 70 mass% or more, preferably 90 mass% or more). By performing the operation in this manner, the target ethanol and water can be largely separated.

[0027] The temperature inside the distillation apparatus during the distillation of ethanol is not particularly limited, but is preferably 100° C. or lower, and more preferably about 70 to 95° C. By setting the temperature inside the distillation apparatus within the above range, it is possible to reliably separate ethanol from other components such as water. The pressure inside the distillation apparatus during the distillation of ethanol may be normal pressure, but is preferably less than atmospheric pressure, more preferably about 60 to 150 kPa (gauge pressure). By setting the pressure inside the distillation apparatus within the above range, the separation efficiency of ethanol can be improved, and the ethanol yield can be improved.

[0028] <Electrolysis> Ethylene glycol can be produced from carbon dioxide gas by electrolysis. A method for producing ethylene glycol from carbon dioxide gas by electrolysis will be described below.

[0029] Electrolysis can be carried out, for example, using an electrolysis cell that includes an anode, a cathode, and an ion exchange membrane disposed to separate the anode and the cathode.

[0030] The anode oxidizes water (HO) to produce oxygen (O) and hydrogen ions (H + ) is generated. Alternatively, hydroxide ions (OH -) to generate oxygen (O2) and water (H2O). On the other hand, the cathode is charged with hydrogen ions (H + ) and electrons (e - ) to reduce carbon dioxide (CO2) and to produce carbon compounds such as ethylene glycol (C2H6O2). In this way, by reducing carbon dioxide on the cathode side of the electrolysis cell, it is possible to produce ethylene glycol using carbon dioxide as a raw material.

[0031] The anode is preferably mainly composed of a catalytic material capable of reducing the overvoltage of the reaction of oxidizing water or hydroxide ions. Examples of such catalytic materials include metals such as platinum (Pt), palladium (Pd), and nickel (Ni), alloys and intermetallic compounds containing these metals, binary metal oxides such as manganese oxide (Mn-O), iridium oxide (Ir-O), nickel oxide (Ni-O), cobalt oxide (Co-O), iron oxide (Fe-O), tin oxide (Sn-O), indium oxide (In-O), ruthenium oxide (Ru-O), lithium oxide (Li-O), and lanthanum oxide (La-O), ternary metal oxides such as Ni-Co-O, Ni-Fe-O, La-Co-O, Ni-La-O, and Sr-Fe-O, quaternary metal oxides such as Pb-Ru-Ir-O and La-Sr-Co-O, and metal complexes such as Ru complexes and Fe complexes.

[0032] The cathode is preferably made of a catalytic material capable of reducing the overvoltage of the reaction of reducing carbon dioxide. Examples of such catalytic materials include metals such as gold (Au), silver (Ag), copper (Cu), platinum (Pt), palladium (Pd), nickel (Ni), cobalt (Co), iron (Fe), manganese (Mn), titanium (Ti), cadmium (Cd), zinc (Zn), indium (In), gallium (Ga), lead (Pb), and tin (Sn), metal materials such as alloys and intermetallic compounds containing at least one of these metals, carbon materials such as carbon (C), graphene, CNT (carbon nanotube), fullerene, and Ketjen Black, and metal complexes such as Ru complexes and Re complexes.

[0033] <Diol unit> The diol unit used in the present disclosure may not be only ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide. That is, ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide may be used in combination with other diols. Even if it is used in combination with other diols, the use of ethylene glycol made from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide can reduce the environmental load.

[0034] Other diols include diols derived from fossil fuels and diols derived from biomass.

[0035] As the diol derived from fossil fuel, a compound having two or more, preferably two to eight hydroxyl groups in one molecule can be used. Specifically, as the diol derived from fossil fuel, there is no particular limitation and a conventionally known substance can be used, for example, polypropylene glycol (PPG), neopentyl glycol (NPG), ethylene glycol (EG), diethylene glycol (DEG), butylene glycol (BG), hexamethylene glycol, triethylene glycol, dipropylene glycol, 1,4-cyclohexanedimethanol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, etc. can be used. These may be used alone or in combination of two or more.

[0036] As the biomass-derived diol, an aliphatic diol obtained from a plant raw material such as corn, sugarcane, cassava, or sago palm can be used. As the biomass-derived aliphatic diol, for example, polypropylene glycol (PPG), neopentyl glycol (NPG), ethylene glycol (EG), diethylene glycol (DEG), butylene glycol (BG), hexamethylene glycol, etc., which are obtained from a plant raw material by the following method, can be used, and any of them can be used. These may be used alone or in combination.

[0037] Biomass-derived polypropylene glycol is produced by a fermentation method in which glucose is obtained by decomposing plant raw materials, via 3-hydroxypropylaldehyde (HPA) from glycerol. Compared with polypropylene glycol produced by the EO production method, polypropylene glycol produced by a biomethod such as the fermentation method is preferable in terms of safety, since useful by-products such as lactic acid can be obtained, and the production cost can be kept low. Biomass-derived butylene glycol can be produced from biomass-derived succinic acid. Specifically, glycol is produced from a plant raw material, and the glycol is fermented to obtain biomass-derived succinic acid. Biomass-derived butylene glycol can be produced by adding water to biomass-derived succinic acid. Biomass-derived ethylene glycol can be produced, for example, from bioethanol obtained by a conventional method via ethylene.

[0038] <Dicarboxylic acid unit> The dicarboxylic acid unit of the polyester is, for example, a dicarboxylic acid derived from a fossil fuel. As the dicarboxylic acid derived from a fossil fuel, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives thereof can be used without limitation. Examples of aromatic dicarboxylic acids include terephthalic acid and isophthalic acid, and examples of derivatives of aromatic dicarboxylic acids include lower alkyl esters of aromatic dicarboxylic acids, specifically, methyl esters, ethyl esters, propyl esters, butyl esters, etc. Among these, terephthalic acid is preferred, and dimethyl terephthalate is preferred as a derivative of aromatic dicarboxylic acid. In addition, specific examples of the aliphatic dicarboxylic acid include linear or alicyclic dicarboxylic acids having 2 to 40 carbon atoms, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid, and cyclohexanedicarboxylic acid. In addition, examples of the derivatives of the aliphatic dicarboxylic acids include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the above aliphatic dicarboxylic acids, and cyclic acid anhydrides of the above aliphatic dicarboxylic acids, such as succinic anhydride. Among these, adipic acid, succinic acid, dimer acid, or a mixture thereof is preferred, and those mainly composed of succinic acid are particularly preferred. Examples of the derivatives of the aliphatic dicarboxylic acid include methyl esters of adipic acid and succinic acid, or a mixture thereof.

[0039] The dicarboxylic acid used in the dicarboxylic acid unit may be a biomass-derived dicarboxylic acid. As the biomass-derived dicarboxylic acid, aliphatic dicarboxylic acids obtained from plant raw materials such as renewable plant-derived oils such as soybean oil, linseed oil, tung oil, coconut oil, palm oil, castor oil, etc., and regenerated oils obtained by recycling waste edible oils mainly containing these oils can be used. Examples of biomass-derived aliphatic dicarboxylic acids include sebacic acid, succinic acid, phthalic acid, adipic acid, glutaric acid, dimer acid, etc. For example, sebacic acid is produced by alkaline pyrolysis of ricinoleic acid obtained from castor oil, with heptyl alcohol as a by-product. As the aromatic dicarboxylic acid derived from biomass, terephthalic acid derived from biomass can be used. The terephthalic acid derived from biomass can be produced, for example, by producing isobutanol from corn, sugars, or wood, converting the isobutanol into isobutylene, dimerizing the isobutane to produce isooctene, synthesizing p-xylene through radical cleavage, recombination, and cyclization, and then oxidizing the xylene (International Publication No. WO 2009 / 079213). When a biomass-derived dicarboxylic acid is used as the dicarboxylic acid unit, in the present disclosure, it is particularly preferable to use biomass-derived terephthalic acid.

[0040] The dicarboxylic acid unit of the polyester may be a dicarboxylic acid produced from carbon dioxide gas as a raw material. An example of a dicarboxylic acid made from carbon dioxide gas is terephthalic acid made from carbon dioxide gas. Terephthalic acid made from carbon dioxide gas can be produced by, for example, using a composite catalyst containing chromium oxide and a specific H-ZSM-5 zeolite to produce p-xylene from carbon dioxide gas and hydrogen gas as raw materials, and then oxidizing the p-xylene (JP Patent Publication No. 2019-205969).

[0041] These dicarboxylic acids may be used alone or in combination of two or more.

[0042] The polyester contained in the polyester pellet according to the present disclosure may be a copolymer polyester in which a copolymer component is added as a third component in addition to the above diol unit and dicarboxylic acid unit. Specific examples of the copolymer component include bifunctional oxycarboxylic acid, and at least one polyfunctional compound selected from the group consisting of trifunctional or more polyhydric alcohols, trifunctional or more polycarboxylic acids and / or their anhydrides, and trifunctional or more oxycarboxylic acids to form a crosslinked structure. Among these copolymer components, bifunctional and / or trifunctional or more oxycarboxylic acids are particularly preferably used because they can easily produce a copolymer polyester with a high degree of polymerization. Among them, the use of trifunctional or more oxycarboxylic acids is most preferred because they can easily produce a polyester with a high degree of polymerization with a very small amount without using a chain extender described later.

[0043] The polyester may be a high molecular weight polyester obtained by chain-extending (coupling) these copolymer polyesters. As the chain extender, a carbonate compound, a diisocyanate compound or the like may be used, and the amount of the carbonate bond and the urethane bond is usually 10 mol % or less, preferably 5 mol % or less, more preferably 3 mol % or less, based on 100 mol % of all monomer units constituting the polyester.

[0044] Specific examples of carbonate compounds include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, etc. In addition, carbonate compounds composed of the same or different hydroxy compounds derived from hydroxy compounds such as phenols and alcohols can be used.

[0045] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, and isophorone diisocyanate.

[0046] The polyester contained in the polyester pellet according to the present disclosure can be obtained by a conventionally known method of polycondensing the above-mentioned diol unit and dicarboxylic acid unit. Specifically, the polyester can be produced by a general melt polymerization method in which the above-mentioned diol unit and dicarboxylic acid unit are subjected to an esterification reaction and / or an ester exchange reaction, followed by a polycondensation reaction under reduced pressure, or by a known solution heating dehydration condensation method using an organic solvent.

[0047] The amount of diol used in producing the polyester is substantially equimolar to 100 moles of the dicarboxylic acid or its derivative. Generally, however, the diol is used in an excess of 0.1 mol % or more and 20 mol % or less, since distillates are generated during the esterification and / or transesterification reaction and / or condensation polymerization reaction.

[0048] The polycondensation reaction is preferably carried out in the presence of a polymerization catalyst. The timing of adding the polymerization catalyst is not particularly limited as long as it is before the polycondensation reaction, and the catalyst may be added when the raw materials are charged or when the pressure reduction is started.

[0049] The polymerization catalyst generally includes compounds containing metal elements of Groups 1 to 14 of the periodic table, excluding hydrogen and carbon. Specifically, compounds containing organic groups such as carboxylates, alkoxy salts, organic sulfonates, or β-diketonate salts containing at least one metal selected from the group consisting of titanium, zirconium, tin, antimony, cerium, germanium, zinc, cobalt, manganese, iron, aluminum, magnesium, calcium, strontium, sodium, and potassium, and further inorganic compounds such as oxides and halides of the above metals and mixtures thereof. Among these, metal compounds containing titanium, zirconium, germanium, zinc, aluminum, magnesium, and calcium, and mixtures thereof are preferred, and titanium compounds, zirconium compounds, and germanium compounds are particularly preferred. In addition, the catalyst is preferably a compound that is liquid during polymerization or dissolves in an ester oligomer or polyester, because the polymerization rate increases when the catalyst is in a molten or dissolved state during polymerization.

[0050] As the titanium compound, tetraalkyl titanate is preferred, specifically, tetra-n-propyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate, tetra-t-butyl titanate, tetraphenyl titanate, tetracyclohexyl titanate, tetrabenzyl titanate, and mixed titanates thereof can be mentioned. In addition, titanium (oxy) acetylacetonate, titanium tetraacetylacetonate, titanium (diisopropoxide) acetylacetonate, titanium bis (ammonium lactate) dihydroxide, titanium bis (ethylacetoacetate) diisopropoxide, titanium (triethanolamine) isopropoxide, polyhydroxytitanium stearate, titanium lactate, titanium triethanolamine, butyl titanate dimer, etc. can also be preferably used. Furthermore, titanium oxide and composite oxides containing titanium and silicon can also be preferably used. Among these, tetra-n-propyl titanate, tetraisopropyl titanate and tetra-n-butyl titanate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, titanium bis(ammonium lactate) dihydroxide, polyhydroxytitanium stearate, titanium lactate, butyl titanate dimer, titanium oxide, titania / silica composite oxide (e.g., Acordis Industrial Preferred are tetra-n-butyl titanate, polyhydroxytitanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and titania / silica composite oxide (for example, product name C-94 manufactured by Acordis Industrial Fibers) and particularly preferred are tetra-n-butyl titanate, polyhydroxytitanium stearate, titanium (oxy)acetylacetonate, titanium tetraacetylacetonate, and titania / silica composite oxide (for example, product name C-94 manufactured by Acordis Industrial Fibers).

[0051] Specific examples of the zirconium compound include zirconium tetraacetate, zirconium acetate hydroxide, zirconium tris(butoxy)stearate, zirconyl diacetate, zirconium oxalate, zirconyl oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium ethoxide, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, zirconium tetra-t-butoxide, zirconium tributoxyacetylacetonate, and mixtures thereof. Zirconium oxide and composite oxides containing, for example, zirconium and silicon may also be used. Among these, zirconyl diacetate, zirconium tris(butoxy)stearate, zirconium tetraacetate, zirconium acetate hydroxide, ammonium zirconium oxalate, potassium zirconium oxalate, polyhydroxyzirconium stearate, zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetra-n-butoxide, and zirconium tetra-t-butoxide are preferred.

[0052] Specific examples of germanium compounds include inorganic germanium compounds such as germanium oxide and germanium chloride, and organic germanium compounds such as tetraalkoxygermanium. In view of cost and availability, germanium oxide, tetraethoxygermanium, tetrabutoxygermanium, and the like are preferred, with germanium oxide being particularly preferred.

[0053] When using metal compounds as these polymerization catalysts, the amount of catalyst used is usually 5 ppm or more, preferably 10 ppm or more, and the upper limit is usually 30,000 ppm or less, preferably 1000 ppm or less, more preferably 250 ppm or less, and particularly preferably 130 ppm or less, as the amount of metal relative to the polyester produced. If the amount of catalyst used is too large, not only is it economically disadvantageous, but the thermal stability of the polymer is also reduced. If the amount of catalyst used is too small, the polymerization activity is reduced, and decomposition of the polymer is easily induced during the polymer production. As for the amount of catalyst used here, the method of reducing the amount of catalyst used is a preferred embodiment, since the amount of terminal carboxyl groups of the polyester produced is reduced as the amount of catalyst used is reduced.

[0054] The reaction temperature of the esterification reaction and / or transesterification reaction between the diol unit and the dicarboxylic acid unit is usually in the range of 150° C. to 260° C., and the reaction atmosphere is usually an inert gas atmosphere such as nitrogen or argon. The reaction pressure is usually normal pressure to 10 kPa. The reaction time is usually 1 hour to 10 hours.

[0055] In the above-mentioned production process, a chain extender (coupling agent) may be added to the reaction system. After the polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without using a solvent, and reacted with the polyester obtained by the polycondensation.

[0056] High molecular weight polyesters using these chain extenders (coupling agents) can be produced using known techniques. After polycondensation is completed, the chain extender is added to the reaction system in a homogeneous molten state without using a solvent, and reacted with the polyester obtained by polycondensation. Specifically, a polyester prepolymer having a terminal group substantially containing a hydroxyl group and a mass average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more, obtained by catalytic reaction of a diol with a dicarboxylic acid, is reacted with the chain extender to obtain a polyester with a higher molecular weight. If the prepolymer has a mass average molecular weight of 20,000 or more, a small amount of coupling agent is used, and even under harsh conditions such as a molten state, it is not affected by the remaining catalyst, so that a high molecular weight polyester can be produced without generating gel during the reaction.

[0057] [Polyester pellets] The polyester pellets according to the present disclosure can be obtained by molding the polyester obtained as described above by a known method. For example, the polyester is extracted in the form of a strand from a polymerization reaction tank, and pelletized using a fixed or rotary cutter or pelletizer while or after cooling with water or air. The shape of the pellets after molding can be cylindrical with a circular or elliptical cross section, or spherical.

[0058] After the polyester is pelletized, solid-phase polymerization may be carried out as necessary to further increase the degree of polymerization or to remove oligomers such as cyclic trimers. Specifically, the polyester is pelletized and dried, and then pre-crystallized by heating at a temperature of 100° C. to 180° C. for 1 hour to 8 hours, and then heated at a temperature of 190° C. to 230° C. under an inert gas flow or under reduced pressure for 1 hour to several tens of hours.

[0059] The diameter of the polyester pellets is adjusted by adjusting the diameter of the outlet from the polymerization reactor, the strand withdrawal speed, the take-up speed, the cutting speed, etc. Specifically, the diameter is adjusted by adjusting the pressure in the polymerization reactor when the polymer is withdrawn or by adjusting the cutting speed of the rotary strand cutter.

[0060] The diameter of the obtained polyester pellets is usually 0.1 mm or more, preferably 0.2 mm or more, more preferably 0.5 mm or more, and most preferably 1 mm or more, and the upper limit (maximum diameter) is 20 mm or less, preferably 10 mm or less, more preferably 7 mm or less, and most preferably 4 mm or less. If the diameter is too small, degradation due to hydrolysis during pellet storage tends to become significant, and if the diameter is too large, the pellets tend to be poorly inserted during molding, resulting in unevenness in the product. The diameter of the polyester pellet referred to here means the diameter or length of the cross section of the polyester pellet, and the cross section of the polyester pellet means the cross section having the maximum cross-sectional area of ​​the polyester pellet.

[0061] In the polyester pellets according to the present disclosure, the proportion of powders having a maximum diameter of less than 1 mm is preferably 2.0% by weight or less, and more preferably 1.0% by weight or less. If the proportion of powders having a maximum diameter of less than 1 mm is high, the powders will be poorly inserted into the molding machine screw during melt molding, resulting in a long residence time in the molding machine, and will be prone to thermal degradation due to their large surface area, which will be mixed into the molded product as foreign matter such as burns and bumps, leading to problems such as a decrease in the mechanical strength of the molded product and poor appearance.

[0062] The intrinsic viscosity of the polyester pellets according to the present disclosure is 0.50 dL / g or more and 0.90 dL / g or less, preferably 0.60 dL / g or more and 0.85 dL / g or less, more preferably 0.65 dL / g or more and 0.80 dL / g or less. If the intrinsic viscosity is less than 0.50 dL / g, the mechanical properties required for the molded body or film produced using the polyester pellets may be insufficient. On the other hand, if the intrinsic viscosity exceeds 0.90 dL / g, the productivity is impaired in the raw material production process, the molded body production process, and the film production process. The preferred value of the intrinsic viscosity of the polyester pellets according to the present disclosure varies depending on the application of the polyester pellets. For example, when the polyester pellets are used for a molded body, the intrinsic viscosity of the polyester pellets is preferably 0.70 or more, more preferably 0.75 or more, and preferably 0.85 or less, and more preferably 0.80 or less. When the polyester pellets are used for a film, the intrinsic viscosity of the polyester pellets is preferably 0.55 or more, more preferably 0.60 or more, and preferably 0.70 or less, and more preferably 0.65 or less. The intrinsic viscosity of the polyester pellets according to the present disclosure is a value calculated from the melt viscosity measured at 35° C. using a phenol / tetrachloroethane solvent (component ratio: 3 / 2).

[0063] Polyester pellets having a desired intrinsic viscosity can be obtained by adjusting the polycondensation reaction temperature, polycondensation reaction pressure, polycondensation reaction time, solid-phase polymerization temperature, solid-phase polymerization pressure, solid-phase polymerization time, and the like. The higher the temperature of the polycondensation reaction, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the temperature of the polycondensation reaction, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the pressure of the polycondensation reaction, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the pressure of the polycondensation reaction, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The longer the polycondensation reaction time, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the shorter the polycondensation reaction time, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the temperature of the solid-phase polymerization, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the temperature of the solid-phase polymerization, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The higher the pressure of the solid-state polymerization, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the lower the pressure of the solid-state polymerization, the lower the intrinsic viscosity of the resulting polyester pellets tends to be. The longer the solid-state polymerization time, the higher the intrinsic viscosity of the resulting polyester pellets tends to be, whereas the shorter the solid-state polymerization time, the lower the intrinsic viscosity of the resulting polyester pellets tends to be.

[0064] In the polyester pellets according to the present disclosure, the Kjeldahl nitrogen content tends to be smaller than that of conventional polyester pellets derived from fossil fuels.For example, the Kjeldahl nitrogen content in the polyester pellets according to the present disclosure is preferably 260 μg / g or less, more preferably 230 μg / g or less, and even more preferably 200 μg / g or less.In addition, the Kjeldahl nitrogen content in the polyester pellets according to the present disclosure is 0 μg / g or more, practically 100 μg / g or more, and more practically 150 μg / g or more. In the present disclosure, Kjeldahl nitrogen is nitrogen quantified in accordance with JIS K0102:2019 44.1 (Kjeldahl method) and 44.2 (Indophenol blue absorptiometry). The specific method for measuring the content of Kjeldahl nitrogen is measured by the method described in the Examples below.

[0065] In the polyester pellets according to the present disclosure, the carbon dioxide molecule content tends to be higher than that of conventional polyester pellets derived from fossil fuels. For example, the carbon dioxide molecule content in the polyester pellets according to the present disclosure is 4.8×10 17It is preferable that the number of particles is 7.0×10 17 More preferably, it is 1.0×10 18 The content of carbon dioxide molecules in the polyester pellets according to the present disclosure is preferably 3.0×10 18 It is preferable that the number of particles is less than 2.0×10 18 More preferably, it is 1.5×10 18 It is more preferable that the number is not more than 1 / g. The content of carbon dioxide molecules in the polyester pellets is measured by thermal desorption / dissociation mass spectrometry (TDS-MS), specifically, by the method described in the Examples below.

[0066] In addition, the polyester pellets according to the present disclosure tend to have a higher water molecule content than conventional polyester pellets derived from fossil fuels. For example, the water molecule content in the polyester pellets according to the present disclosure is 1.8×10 19 It is preferable that the number of particles is 2.0×10 19 More preferably, the number is 4.0×10 19 The water molecule content in the polyester pellets according to the present disclosure is preferably 1.0×10 20 It is preferable that the number of particles is less than 7.5×10 19 More preferably, it is 5.0×10 19 It is more preferable that the number is not more than 1 / g. The content of water molecules in the polyester pellets is measured by thermal desorption spectrometry-mass spectrometry (TDS-MS), specifically, by the method described in the Examples below.

[0067] In the process of producing polyester pellets or to the produced polyester pellets, various additives may be added within the range that does not impair the properties thereof, such as plasticizers, ultraviolet stabilizers, coloring inhibitors, matting agents, deodorants, flame retardants, weather resistance agents, antistatic agents, thread friction reducing agents, release agents, antioxidants, ion exchange agents, color pigments, etc. These additives are added in the range of 5 to 50% by mass based on the total amount of the polyester pellets.

[0068] The polyester pellets according to the present disclosure can be used to produce molded articles or films, as described below. However, the uses of the polyester pellets according to the present disclosure are not limited thereto, and for example, the polyester pellets can be used to produce fibers, but do not necessarily have to be used to produce fibers.

[0069] [Molded body] The molded article according to the present disclosure is made using the polyester pellets. The molded article may be a compression molded article, an injection molded article, a blow molded article, a thermoformed article, or the like. Specific examples of the container include a bottle, a vial, a cup, a tray, and a pack. The polyester pellets can be processed into a molded product by a conventional method for processing polyester pellets into a molded product. An example of a method for processing polyester pellets into a bottle will be described below.

[0070] The polyester pellets are melted and injected into an injection molding machine to produce a preform 30 as shown in FIG.

[0071] 1 includes a mouth portion 31, a body portion 32 connected to the mouth portion 31, and a bottom portion 33 connected to the body portion 32. Of these, the mouth portion 31 corresponds to the mouth portion 41 of a bottle 40 described later, and has substantially the same shape as the mouth portion 41. The body portion 32 corresponds to the neck portion 44, shoulder portion 48, and body portion 42 of the bottle 40, and has a substantially cylindrical shape. The bottom portion 33 corresponds to the bottom portion 43 of the bottle 40, and has a substantially hemispherical shape.

[0072] In one embodiment, the mouth 31 includes a threaded portion 34 that corresponds to a threaded portion 46 of the bottle 40 to which the cap is screwed, a cap 35 provided below the threaded portion 34, and a support ring 36 provided below the cap 35 and that corresponds to a support ring 47 of the bottle 40. The shape of the mouth 31 may be a conventionally known shape.

[0073] Next, the preform is heated and subjected to biaxial stretch blow molding in a blow molding die, thereby forming a bottle as shown in FIG.

[0074] The bottle 40 shown in Fig. 2 has a mouth 41, a substantially cylindrical body 42, and a bottom 43. The body 42 is provided below and continuous with the mouth 41. The bottom 43 is provided below and continuous with the body 42. A neck 44 is located between the mouth 41 and the body 42. A shoulder 48 is located between the neck 44 and the body 42.

[0075] A threaded portion 46 for screwing a cap (not shown) is provided on the outer periphery of the mouth portion 41. A ring-shaped support ring 47 that protrudes outward is provided on the outer periphery of the mouth portion 41 below the threaded portion 46.

[0076] As described above, the body 42 is substantially cylindrical. A plurality of horizontal grooves 45 are formed in the body 42. The horizontal cross section of the shoulder 48 is substantially circular, and the area of ​​the horizontal cross section of the shoulder 48 gradually increases from the neck 44 side toward the body 42 side.

[0077] A heel portion 49 is formed on the radially outer portion of the bottom portion 43. The heel portion 49 is provided in an annular shape over the entire circumferential area of ​​the bottom portion 43. The heel portion 49 is the portion of the bottom portion 43 that is stretched to be the thinnest during blow molding.

[0078] The size of the bottle 40 is not limited, and the bottle may be of any size. The full capacity of the bottle 40 may be, for example, 100 mL or more, 200 mL or more, or 300 mL or more. The full capacity of the bottle 40 may be, for example, 600 mL or less, 550 mL or less, or 530 mL or less.

[0079] Furthermore, the thickness of the heel portion 49 of the bottom 43 is not limited to this, but may be, for example, 0.07 mm or more, 0.08 mm or more, or 0.09 mm or more. The thickness of the heel portion 49 may be, for example, 0.30 mm or less, 0.25 mm or less, or 0.20 mm or less. By making the thickness of the heel portion 49 0.30 mm or less, the weight of the bottle 40 can be reduced. On the other hand, by making the thickness of the heel portion 49 0.07 mm or more, it is possible to prevent the bottom 43 from popping out and becoming permanently deformed when the bottle 40 is placed in a vending machine or dropped.

[0080] From the standpoint of bottle strength, the cross-sectional thickness of body 42 of bottle 40 is preferably 0.05 mm or more, and more preferably 0.10 mm or more. On the other hand, from the viewpoint of reducing the amount of polyester used, the cross-sectional thickness of the body 42 of the bottle 40 is preferably 0.54 mm or less, and more preferably 0.50 mm or less. The cross-sectional thickness of the body 42 of the bottle 40 refers to the cross-sectional thickness of the bottle 40 at the point in the body 42 where the cross-sectional thickness is the smallest.

[0081] In the bottle according to one embodiment of the present disclosure, the ratio of volume to mass (volume / mass) is preferably 5 mL / g or more, and more preferably 8 mL / g or more, from the viewpoint of moldability of the bottle. On the other hand, the volume / mass is preferably 50 mL / g or less, and more preferably 45 mL / g or less, from the viewpoint of the strength of the bottle.

[0082] The bottle according to one embodiment of the present disclosure may have a single-layer structure or a multi-layer structure of two or more layers. In addition, when the bottle has a multi-layer structure, each layer may have the same composition or different compositions.

[0083] In one embodiment, the bottle may have a vapor-deposited film on its surface. This can improve the gas barrier properties of the bottle. The vapor-deposited film may be located on the inner surface or the outer surface of the bottle, but is preferably located on the inner surface.

[0084] Examples of the vapor-deposited film include vapor-deposited films composed of metals such as aluminum, inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide, organic silicon compounds such as hexamethyldisiloxane, and hard carbon films such as DLC (Diamond Like Carbon) films. In addition, the hard carbon film made of DLC is also called i-carbon film or hydrogenated amorphous carbon film (aC:H), and is a hard carbon film. 3 It is an amorphous carbon film that is mainly composed of bonds.

[0085] The thickness of the deposited film is not particularly limited, and can be, for example, 1 nm or more and 150 nm or less.

[0086] The deposition film can be formed by a conventional method, for example, physical vapor deposition methods (PVD method) such as vacuum deposition method, sputtering method, and ion plating method, and chemical vapor deposition methods (CVD method) such as plasma chemical vapor deposition method, thermal chemical vapor deposition method, and photochemical vapor deposition method. The thickness of the vapor-deposited film can be measured at the body of the bottle, and means the thickness of the cross section of the vapor-deposited film at the point where the cross section has the smallest thickness. When the vapor-deposited film is multi-layered, the thickness of the vapor-deposited film is the sum of the thicknesses of all the vapor-deposited films.

[0087] [film] The film according to the present disclosure uses the polyester pellets described above. To process the polyester pellets into a film, a conventional method for forming a film from polyester pellets can be adopted. Specifically, the polyester pellets described above are dried, and then fed into a melt extruder heated to a temperature (Tm) to Tm+70°C above the melting point of the polyester pellets to melt the polyester pellets. The molten polyester pellets are extruded into a sheet shape from a die such as a T-die. The extruded sheet-like material is quenched and solidified by a rotating cooling drum or the like. In this manner, a film 1 as shown in FIG. 3 can be formed. As the melt extruder, a single screw extruder, a twin screw extruder, a vent extruder, a tandem extruder, etc. can be used depending on the purpose.

[0088] The film according to the present disclosure is preferably biaxially stretched. The biaxial stretching can be carried out by a conventionally known method, and may be sequential biaxial stretching or simultaneous biaxial stretching. Sequential biaxial stretching and simultaneous biaxial stretching will be described below.

[0089] [Sequential biaxial stretching] In the sequential biaxial stretching, the film extruded onto the cooling drum as described above is stretched in the machine direction, and then the film is stretched in the transverse direction. The longitudinal stretching is usually performed by the difference in peripheral speed of rolls, and may be performed in one step or in multiple steps using a plurality of pairs of rolls. The longitudinal stretching ratio is preferably 2.0 times or more, more preferably 2.5 times or more, and is preferably 15.0 times or less, more preferably 7.0 times or less, even more preferably 5.0 times or less, and even more preferably 4.2 times or less. This can suppress the variation in optical properties such as in-plane retardation. The stretching temperature is preferably 50° C. or higher, more preferably 80° C. or higher, and even more preferably 95° C. or higher, and is preferably 120° C. or lower, more preferably 115° C. or lower, and even more preferably 110° C. or lower, which can suppress variations in optical properties such as in-plane retardation.

[0090] The stretching in the transverse direction is usually performed by using a tenter method, in which the film is conveyed while both ends of the film are held by clips, and stretched in the transverse direction. The stretching ratio in the transverse direction is preferably 2 times or more, more preferably 2.5 times or more, and is preferably 15 times or less, more preferably 5 times or less. This can suppress the variation in optical properties such as in-plane retardation. The stretching temperature is preferably 50° C. or higher, more preferably 90° C. or higher, and even more preferably 95° C. or higher, and is preferably 120° C. or lower, more preferably 110° C. or lower, and even more preferably 105° C. or lower, which can suppress variations in optical properties such as in-plane retardation.

[0091] The film sequentially biaxially stretched as described above is preferably subjected to heat treatment in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in order to impart planarity and dimensional stability. Specifically, it is preferable to perform heat fixing at a temperature of preferably 120°C or higher, more preferably 190°C or higher, and preferably 235°C or lower, more preferably 225°C or lower. In addition, from the viewpoint of suppressing the variation in optical properties such as in-plane retardation, it is preferable to perform heat treatment post-stretching of 1% to 10% in the first half of the heat treatment. This can suppress the variation in optical properties such as in-plane retardation. After the film is heat-treated, it is slowly cooled to room temperature and then wound up. If necessary, a relaxation treatment or the like may be used in combination with the heat treatment or the slow cooling. The relaxation rate during the heat treatment is preferably 0.5% or more, more preferably 0.8% or more, even more preferably 1% or more, and preferably 5% or less, more preferably 3% or less, even more preferably 2.5% or less, and even more preferably 2% or less. This can suppress the variation in optical properties such as in-plane retardation. The relaxation rate during slow cooling is preferably 0.5% or more, and more preferably 3% or less, more preferably 2% or less, even more preferably 1.5% or less, and even more preferably 1.0% or less. This can suppress the variation in optical properties such as in-plane retardation. From the viewpoint of flatness, the temperature during slow cooling is preferably 80°C or more, more preferably 90°C or more, and even more preferably 100°C or more, and also preferably 150°C or less, more preferably 130°C or less, and even more preferably 120°C or less.

[0092] [Simultaneous biaxial stretching] In the simultaneous biaxial stretching, the film extruded onto the cooling drum as described above is introduced into a simultaneous biaxial tenter, and while both ends of the film are held by clips, the film is conveyed and stretched simultaneously and / or stepwise in the longitudinal and transverse directions. The simultaneous biaxial stretching machine may be of the pantograph type, screw type, drive motor type, or linear motor type, but the drive motor type or linear motor type is preferred, since it is possible to change the stretch ratio at any desired position and perform relaxation treatment at any desired position.

[0093] The area ratio of the simultaneous biaxial stretching is preferably 2 times or more, more preferably 3 times or more, even more preferably 6 times or more, even more preferably 10 times or more, and is preferably 50 times or less, more preferably 30 times or less, even more preferably 25 times or less, even more preferably 20 times or less, and particularly preferably 15 times or less, which can suppress variations in optical properties such as in-plane retardation. In the case of simultaneous biaxial stretching, in order to suppress differences in in-plane orientation, it is preferable that the stretching ratios in the machine direction and the cross direction are the same, and that the stretching speeds are also approximately the same.

[0094] The stretching temperature in the simultaneous biaxial stretching is preferably 50° C. or higher, more preferably 90° C. or higher, and even more preferably 100° C. or higher, and is preferably 160° C. or lower, more preferably 150° C. or lower, and even more preferably 140° C. or lower, thereby making it possible to suppress variations in optical properties such as in-plane retardation.

[0095] The simultaneously biaxially stretched film is preferably subsequently subjected to a heat treatment at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point in a heat fixing chamber in a tenter in order to impart flatness and dimensional stability to the film. The heat treatment conditions are the same as those after the successive biaxial stretching.

[0096] The thickness of the film according to the present disclosure is arbitrary depending on the application, but is usually 5 μm or more and 500 μm or less. The breaking strength of such a film is 1 kg / mm ​​in the MD direction. 2 More than 40kg / mm 2 Below, 1kg / mm ​​in TD direction 2 More than 35kg / mm 2 The elongation at break is 10% to 350% in the MD direction and 3% to 300% in the TD direction. Thus, the film according to the present disclosure has physical properties equivalent to those of polyester films produced from conventional fossil fuel-derived materials or biomass-derived materials.

[0097] The film according to the present disclosure may be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, biocompatibility, etc. Examples of secondary processing include embossing, painting, adhesion, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), etc.

[0098] The film according to the present disclosure can be suitably used for applications such as laminates, packaging materials, various label materials, lid materials, sheet molded products, and laminate tubes. EXAMPLES

[0099] The present disclosure will be described more specifically below with reference to examples, but the present disclosure is not limited to the following examples.

[0100] <Preparation of polyester pellets for film and film> [Example 1] A medium for microbial fermentation was prepared containing the following components in 1 L of distilled water. (Medium composition) 0.5g MgCl2 6H2O 0.2g NaCl 100mM sodium phosphate buffer pH 6.0 160mL 0.6g NH4Cl 0.05mL 85% H3PO4 0.15g KCl ·Trace metal complex solution (LS06) 10mL Vitamin B Complex Solution (LS03) 10mL 1000mg / L Resazurin 1mL 0.0025g FeCl3 · Cysteine ​​HCl monohydrate 0.75g 15g agarose 100 mM sodium phosphate buffer solution was prepared by dissolving 13.2 g of NaH2PO4 and 1.1 g of Na2HPO4·7H2O in 1 L of water.

[0101] In addition, a Clostridium autoethanogenum culture was prepared as a culture for microbial fermentation. The Clostridium autoethanogenum in the culture was obtained from the German Resource Centre for Biological Material (DSMZ), and the accession number given to the bacterium is DSMZ10061.

[0102] A 5 L continuous stirred tank reactor was charged with 4.9 L of the above medium. The headspace gas of the continuous stirred tank reactor was switched to 95% CO, 5% CO2 at atmospheric pressure. 100 mL of Clostridium autoethanogenum culture was inoculated. The continuous stirred tank reactor was maintained at 37 °C and stirred at 200 rpm at the beginning of the culture and 400 rpm during the growth phase. During stirring, the pH of the culture was maintained at 5.5 by automatic addition of 5 M NaOH.

[0103] A sterile serum bottle with a volume of 234 mL was purged three times with steel mill waste gas (composition: 53% CO, 18% CO2, 26% N2, 3% H2) and then evacuated to a vacuum of -5 psi. 50 mL of the above culture was directly transferred into the serum bottle. The head space of the serum bottle was filled with the above waste gas and pressurized to 25 psig while maintaining the reaction temperature at 37°C using a shaking incubator. The culture was incubated at 37°C with shaking. After 5 hours, the ethanol concentration of the culture was 1.675 g / L, confirming the production of ethanol by microbial fermentation.

[0104] The culture solution after microbial fermentation was separated into solid and liquid components using a solid-liquid separation filter device under conditions of a culture solution introduction pressure of 200 kPa or more. The liquid component was then introduced into a distillation apparatus equipped with a heater using steam at 170° C. The temperature of the bottom of the distillation column was raised to 101° C. within 15 minutes, and the liquid component was then introduced into the middle of the distillation column. During continuous operation, the column was operated continuously at 101° C. at the bottom, 99° C. at the middle, and 91° C. at the top at 15 sec / L to purify ethanol.

[0105] Purified ethanol was supplied to a multi-tube, externally heated, isothermal reactor packed with 1.5 L of γ-AlO catalyst (3 mmΦ×3 mmH) at a rate of 10 L / Hr and a pressure of 10 kg / cm 2 G. The reaction was carried out at 370°C for 500 hours, and ethylene was produced by the intramolecular dehydration reaction of ethanol.

[0106] The produced ethylene was introduced into an ethylene oxidation reactor and catalytically oxidized in gas phase with a molecular oxygen-containing gas in the presence of a silver catalyst to obtain a reaction product gas containing ethylene oxide. The reaction product gas containing ethylene oxide was supplied to the lower part of the ethylene oxide absorption tower, and water was introduced from the upper part of the ethylene oxide absorption tower and brought into countercurrent contact with the reaction product gas, so that the ethylene oxide in the reaction product gas was absorbed in the water. The unabsorbed gas near the top of the ethylene oxide absorption tower was circulated to the ethylene oxidation reaction apparatus. The bottom liquid of the ethylene oxide absorption tower was supplied to the upper part of the ethylene oxide stripper tower, the top pressure of which was 0.045 MPa (gauge) and the bottom temperature of which was 115°C. A part of the bottom liquid of the ethylene oxide absorption tower was circulated to the ethylene oxide absorption tower. The vapor stripped near the top of the ethylene oxide stripper was condensed in a condenser, a part of which was refluxed to the ethylene oxide stripper and a part of which was supplied to the ethylene oxide dehydration tower. The vapor near the top of the ethylene oxide dehydration tower was condensed in a condenser, a part of the condensate was refluxed to the dehydration tower, and the remainder of the condensate was supplied to the light fraction separation tower. The vapor near the top of the light fraction separation column was sent to a condenser, and the condensate was refluxed to the light fraction separation column. The bottom liquid of the light fraction separation column was fed to the ethylene oxide fractionator. Ethylene oxide vapor near the top of the ethylene oxide rectification column was condensed in a condenser, a part of which was refluxed to the ethylene oxide rectification column, and the remainder was withdrawn as ethylene oxide.

[0107] The extracted ethylene oxide was added to the bottom liquid of the ethylene oxide dehydration tower and fed to a hydration reactor. The reaction was carried out at a pressure of 1.8 MPa (gauge) and a reaction temperature of 150° C. to obtain a 15.2% by mass ethylene glycol aqueous solution. The aqueous ethylene glycol solution was fed to a first evaporator operated at a top pressure of 0.41 MPa gage and a bottom temperature of 153°C. The bottom liquid of the first evaporator was fed to a second evaporator operated at a top pressure of 0.17 MPa gage and a bottom temperature of 136°C. The bottom liquid of the second evaporator was fed to a third evaporator operated at a top pressure of 0.07 MPa gage and a bottom temperature of 124°C. The bottom liquid of the third evaporator was fed to a fourth evaporator operated at a top pressure of -0.03 MPa gage and a bottom temperature of 105°C. The bottom liquid of the fourth evaporator was fed to an ethylene glycol dehydration column, where water was removed, and then fed to an ethylene glycol distillation column. Ethylene glycol was separated from the top of the ethylene glycol distillation column.

[0108] 62 parts by mass of ethylene glycol derived from carbon monoxide gas thus obtained and 83 parts by mass of terephthalic acid derived from fossil fuel were fed as a slurry to a reaction vessel, and an esterification reaction was carried out at 240°C for 5 hours by a conventional direct polymerization method. Then, 0.013 parts by mass of trimethyl phosphate (manufactured by Aldrich) was added (15 mmol% relative to the acid component), and then the polymerization reaction was transferred to a high-temperature vacuum condition. First, the degree of vacuum was raised to 4000 Pa and the polymerization temperature to 280°C in 40 minutes, and then the degree of vacuum was lowered to 200 Pa while keeping the polymerization temperature at 280°C, and a melt polymerization reaction was carried out for 3 hours to synthesize a polyester. The synthesized polyester was discharged in the form of a strand into running water and pelletized by a pelletizer. The pellets were dried at 160°C for 5 hours, and then solid-phase polymerized at 205°C under a nitrogen atmosphere and a vacuum of 50 Pa. When the melt viscosity reached a value equivalent to an intrinsic viscosity of 0.61, the pellets were discharged to obtain polyester pellets of Example 1. The polyester pellets of Example 1 were dried, fed to an extruder, melted at 260° C., extruded from a T-die into a sheet, and cooled and solidified by a cooling roll to obtain an unstretched sheet. Next, this unstretched sheet was held in an 88°C environment for 1 minute, and then simultaneously stretched in the machine and cross directions at a speed of 100 mm / min at an areal stretching ratio of 3.6 times to obtain a film of Example 1 having a thickness of 12 μm.

[0109] [Example 2] Polyester pellets of Example 2 and a film of Example 2 were obtained in the same manner as in Example 1, except that the time point at which the pellets were discharged in the solid-state polymerization was changed from the time point at which the melt viscosity reached an intrinsic viscosity of 0.61 to the time point at which the melt viscosity reached an intrinsic viscosity of 0.65.

[0110] [Comparative Example 1] Polyester pellets of Comparative Example 1 and a film of Comparative Example 1 were obtained in the same manner as in Example 1, except that ethylene glycol derived from a fossil fuel was used instead of ethylene glycol derived from carbon monoxide gas.

[0111] [Comparative Example 2] Polyester pellets of Comparative Example 2 and a film of Comparative Example 2 were obtained in the same manner as in Example 2, except that ethylene glycol derived from fossil fuels was used instead of ethylene glycol derived from carbon monoxide gas.

[0112] [Measurement of intrinsic viscosity] The melt viscosity of each of the polyester pellets of Examples 1 and 2 and Comparative Examples 1 and 2 was measured at 35° C. using a phenol / tetrachloroethane (component ratio: 3 / 2) solvent, and the intrinsic viscosity was calculated from the melt viscosity. The results are shown in Table 1.

[0113] [Measurement of carbon dioxide and water molecule content] Each of the polyester pellets of Examples 1 and 2 and Comparative Examples 1 and 2 was cut to obtain a 35 mg test piece. The test piece was subjected to thermal desorption gas-mass spectrometry (TDS-MS) under the following measurement conditions to measure the content of carbon dioxide molecules and water molecules contained in the polyester pellets. The results are shown in Table 1. (Measurement conditions) ·Device name: Denshi Kagaku EMD-WA1000S / W type Heating the specimen on the SiC stage Ionization method: Electron Ionization (EI) Measurement mode: SCAN mode Mass range (m / z): 1 to 200 ·Heating conditions: 50℃~100℃ Heating rate: 10℃ / min Holding temperature and holding time: 100℃ for 30 minutes

[0114] [Haze measurement] Test pieces measuring 50 mm long x 50 mm wide were cut out from each of the films of Examples 1 and 2 and Comparative Examples 1 and 2. The haze of each test piece was measured using a haze meter (NDH4000, manufactured by Nippon Denshoku Industries Co., Ltd.) under an environment of a temperature of 23°C and a relative humidity of 50 RH%. The measurement was performed in accordance with JIS K7136:2000. The smaller the haze, the more transparent the film is. The results are shown in Table 1.

[0115] [Measurement of tensile strength and tensile elongation] Test pieces measuring 200 mm in the machine direction (MD) × 15 mm in the transverse direction (TD) were cut out from each of the films of Examples 1 and 2 and Comparative Examples 1 and 2. The tensile strength and tensile elongation in the machine direction were measured for each test piece using a tensile tester (Tensilon RTC-125A, manufactured by Orientec Co., Ltd.) at a temperature of 23°C and a relative humidity of 50 RH%. The measurement was performed at a tensile speed of 300 mm / min. Further, test pieces measuring 15 mm in the longitudinal direction × 200 mm in the transverse direction were cut out, and the tensile strength and tensile elongation in the transverse direction were measured for each test piece in the same manner as above. The results are shown in Table 1.

[0116] [Table 1]

[0117] As is clear from Table 1 above, the polyester pellets of the present disclosure contain more carbon dioxide molecules and water molecules than conventional polyester pellets that use ethylene glycol derived from fossil fuels. It is also clear that the film using the polyester pellets according to the present disclosure exhibits physical properties that are comparable in terms of transparency and mechanical properties to conventional films made from polyesters containing ethylene glycol derived from fossil fuels as a diol unit.

[0118] <Preparation of polyester pellets for molding and molding> [Example 3] The polyester pellets of Example 3 were obtained in the same manner as in Example 1, except that the time point of discharging the pellets in the solid-state polymerization was changed from the time point when the melt viscosity reached an intrinsic viscosity of 0.61 to the time point when the melt viscosity reached an intrinsic viscosity of 0.77. The polyester pellets of Example 3 were fed into an injection molding machine and melted at 290°C, and the melt was then injected to produce the preform shown in Figure 1. The body of the preform had a thickness of 3.5 mm and a basis weight of 22 g. Next, the preform was heated to 110° C. and subjected to biaxial stretch blow molding in a blow molding die to produce a bottle with a full capacity of 600 mL as shown in Figure 2. The cross-sectional thickness of the body of the bottle was 0.28 mm. In this manner, a molded product of Example 3 in the form of a bottle was obtained.

[0119] [Example 4] The polyester pellets of Example 4 and the molded body of Example 4 were obtained in the same manner as in Example 1, except that the time point of discharging the pellets in the solid-state polymerization was changed from the time point when the melt viscosity reached an intrinsic viscosity of 0.61 to the time point when the melt viscosity reached an intrinsic viscosity of 0.79.

[0120] [Comparative Example 3] Polyester pellets of Comparative Example 3 and a molded article of Comparative Example 3 were obtained in the same manner as in Example 3, except that ethylene glycol derived from a fossil fuel was used instead of ethylene glycol derived from carbon monoxide gas.

[0121] [Comparative Example 4] Polyester pellets of Comparative Example 4 and a molded article of Comparative Example 4 were obtained in the same manner as in Example 4, except that ethylene glycol derived from a fossil fuel was used instead of ethylene glycol derived from carbon monoxide gas.

[0122] [Measurement of intrinsic viscosity] The melt viscosity of each of the polyester pellets of Examples 3 and 4 and Comparative Examples 3 and 4 was measured at 35° C. using a phenol / tetrachloroethane (component ratio: 3 / 2) solvent, and the intrinsic viscosity was calculated from the melt viscosity. The results are shown in Table 2.

[0123] [Measurement of Kjeldahl nitrogen content] The content of Kjeldahl nitrogen contained in the polyester pellets of Examples 3 and 4 and Comparative Examples 3 and 4 was measured in accordance with JIS K0102:2019 44.1 (Kjeldahl method) and 44.2 (Indophenol blue absorptiometry). The results are shown in Table 2.

[0124] [Measurement of carbon dioxide molecule content] The polyester pellets of Examples 3 and 4 and Comparative Examples 3 and 4 were each cut to obtain a 35 mg test piece. The test piece was subjected to thermal desorption gas-mass spectrometry (TDS-MS) under the following measurement conditions to measure the content of carbon dioxide molecules contained in the polyester pellets. The results are shown in Table 2. (Measurement conditions) ·Device name: Denshi Kagaku EMD-WA1000S / W type Heating the specimen on the SiC stage Ionization method: Electron Ionization (EI) Measurement mode: SCAN mode Mass range (m / z): 1 to 200 ·Heating conditions: 50℃~100℃ Heating rate: 10℃ / min Holding temperature and holding time: 100℃ for 30 minutes

[0125] [Measurement of buckling strength] The molded bodies of Examples 3 and 4 and Comparative Examples 3 and 4 were filled with 600 mL of water as the liquid content, then sealed with a cap, and a buckling strength test was performed with each molded body in an upright position. A top load tester (buckling test device) EH-1000 manufactured by Ebic Co., Ltd. was used to measure the buckling strength. The molded body was placed upright on a support table, the detection head was moved downward, and a load was applied from above the mouth of the molded body at a constant speed. The maximum load at which the molded body reached a so-called yield state was taken as the buckling strength. The higher the buckling strength, the more excellent the mechanical properties of the molded body. The results are shown in Table 2.

[0126] [Table 2]

[0127] As is clear from Table 2 above, the polyester pellets of the present disclosure have a lower Kjeldahl nitrogen content and a higher carbon dioxide molecule content than conventional polyester pellets using ethylene glycol derived from fossil fuels. It is also clear that the molded body using the polyester pellets according to the present disclosure exhibits physical properties that are comparable in terms of mechanical properties to conventional molded bodies made from polyesters containing ethylene glycol derived from fossil fuels as diol units. [Explanation of symbols]

[0128] 1. Film 30 Preform 31 Mouth 32 Torso 33 Bottom 34 Screw part 35 Turnip 36 Support Ring 40 Bottles 41 Mouth 42 Torso 43 Bottom 44 Neck 45 horizontal groove 46 Screw part 47 Support Ring 48 Shoulder 49 Heel

Claims

1. A polyester pellet comprising a polyester consisting of a diol unit and a dicarboxylic acid unit, The diol unit contains ethylene glycol produced from at least one gas selected from the group consisting of carbon monoxide and carbon dioxide, A polyester pellet having an intrinsic viscosity of 0.50 dL / g or more and 0.90 dL / g or less.

2. 2. The polyester pellet according to claim 1, wherein the dicarboxylic acid unit comprises at least one selected from the group consisting of terephthalic acid derived from a fossil fuel, terephthalic acid derived from biomass, and terephthalic acid derived from carbon dioxide gas.

3. 3. The polyester pellet according to claim 1 or 2, having a Kjeldahl nitrogen content of 260 μg / g or less.

4. The carbon dioxide molecule content is 4.8 x 10 17 pieces / g or more 3.0×10 18 The polyester pellet according to claim 1 or 2, wherein the number of particles per gram is not more than 1.

5. The water molecule content is 1.8 x 10 19 pieces / g or more 1.0×10 20 The polyester pellet according to claim 1 or 2, wherein the number of particles per gram is not more than 1.

6. A molded article using the polyester pellets according to claim 1 or 2.

7. A film using the polyester pellets according to claim 1 or 2.

Citation Information

Patent Citations

  • Microbial alcohol production process

    JP2011512869A

  • Bio-based polyethylene terephthalate polymer and method for producing the same

    JP2011527348A

  • Bio-based polyethylene terephthalate packaging and method for manufacturing the same

    JP2012519748A

  • Electrolytic cell of carbon dioxide and electrolytic apparatus

    JP2018123390A